2016
DOI: 10.5966/sctm.2015-0094
|View full text |Cite
|
Sign up to set email alerts
|

Xeno-Free Extraction, Culture, and Cryopreservation of Human Adipose-Derived Mesenchymal Stem Cells

Abstract: Molecules of animal or bacterial origin, which pose a risk for zoonoses or immune rejection, are commonly used for extraction, culture, and cryopreservation of mesenchymal stem cells. There is no sequential and orderly protocol for producing human adipose-derived stem cells (hASCs) under xeno-free conditions. After standardizing a human platelet lysate (hPL) production protocol, four human adipose tissue samples were processed through explants with fetal bovine serum (FBS)-supplemented or hPLsupplemented media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 58 publications
1
13
0
1
Order By: Relevance
“…In the vast majority of reports the ability of hMSCs to be differentiated along pre-determined lineages was not affected by being cultured using hPL: adipogenic, osteogenic and chondrogenic differentiation were demonstrated with no relevant difference in effectiveness or potential to the same hMSCs cultured with FBS. In three cases MSCs, expanded in hPL, were more effectively differentiated along osteogenic, chondrogenic and adipogenic routes [ 37 , 49 , 58 ]; others reported a difference only for osteogenic [ 17 , 40 , 42 , 47 , 54 ] or adipogenic differentiation respectively [ 19 , 31 ]. Only one publication reported that FBS supported osteogenic and adipogenic differentiation to a higher degree [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the vast majority of reports the ability of hMSCs to be differentiated along pre-determined lineages was not affected by being cultured using hPL: adipogenic, osteogenic and chondrogenic differentiation were demonstrated with no relevant difference in effectiveness or potential to the same hMSCs cultured with FBS. In three cases MSCs, expanded in hPL, were more effectively differentiated along osteogenic, chondrogenic and adipogenic routes [ 37 , 49 , 58 ]; others reported a difference only for osteogenic [ 17 , 40 , 42 , 47 , 54 ] or adipogenic differentiation respectively [ 19 , 31 ]. Only one publication reported that FBS supported osteogenic and adipogenic differentiation to a higher degree [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreservation is currently the best way for long‐term cell storage; MSCs, isolated by explant method, can be successfully revitalized after cryopreservation while maintaining their characteristics . In addition, after cryopreservation of UC tissue, it is possible to isolate MSCs by explant method from post‐thaw tissue pieces …”
Section: Comparison Of Mscs Isolated By Enzymatic and Explant Methodsmentioning
confidence: 99%
“…For removing animal serum from MSC culture, it is suggested to use human serum obtained from the donor, volunteers or UC blood . Human platelet lysate is also recently recommended to be used instead of animal serum …”
Section: Research In Progress and Future Directionsmentioning
confidence: 99%
“…Several groups have evaluated these different PRF or PRP preparations, studying growth factor concentrations , , the effect of leukocytes , and the variability between donors . Finally, recent studies comparing platelet lysate, defined xenobiotic‐free supplements, and FBS have been published .…”
Section: Clinical Studies Of Msc Therapymentioning
confidence: 99%